Integrating Peer – Teacher Corrective Feedback in Writing Instruction in a Private Teachers College in Nagekeo – East Nusa Tenggara - Simon Petrus Kita Ngatu (Universitas Muhammadiyah Kalimantan Timur, 2020)
This article aims at describing the process of applying the model of integrating peer-teacher corrective feedback in order to improve writing instruction in one of private teachers colleges in Nagekeo – East Nusa Tenggara. The research was designed by employing a Classroom Action Research (CAR) which was conducted within two cycles. The process of the research embraced a preliminary reflection, planning, actions, observations, and reflections. The research was conducted in one of the private teachers college in Nagekeo – East Nusa Tenggara and the participants of the study were the second semester students of English Study Program. They consisted of six students. The data were collected through a preliminary observation, interviews, writing tests, and field notes. The research was guided by several prominent studies under the issues of corrective feedback. Based on the data obtained, this study has identified that the implementation of peer – teacher corrective feedback improved the writing instruction in one of the private teachers college in Nagekeo – East Nusa Tenggara.